Psychodynamic therapy in Canada in the era of evidence-based practice. Issue 2 (2nd April 2020) - Abbass, Allan A.; Tasca, Giorgio A.; Vasiliadis, Helen-Maria; Spagnolo, Jessica; Kealy, David; Hewitt, Paul L.; Hébert, Catherine; Drapeau, Martin; Doidge, Norman
Abstract : In this article, Canadian psychotherapy researchers and teachers review the state of psychodynamic therapy (PDT) in Canada. We review the ways in which PDT has been implemented, developed and researched within the public and private sector, and how psychoanalytic and psychodynamic practitioners regionally have responded to the challenges of evidence-based practice and the emphasis on empirically supported treatments (EST) as it is defined today. We note that neglect and misrepresentation of the scientific evidence behind PDT has resulted in its marginalization. There is also a dearth of evidence collected to measure the effectiveness of implementing EST. Based on its empirical standing, we propose a model of care that incorporates PDT as an effective, evidence-based model for first line treatment, and also as an alternative for those patients who do not respond to other treatments or who express a preference for PDT or insight-oriented therapy.